1987
DOI: 10.1172/jci113083
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide release by alveolar macrophages from sarcoid patients and by alveolar macrophages from normals after exposure to recombinant interferons alpha A, beta, and gamma and 1,25-dihydroxyvitamin D3.

Abstract: We measured H202 release by human alveolar macrophages (AM) from normals and sarcoid patients in suspension immediately after bronchoalveolar lavage in the presence and absence of the triggering agent, phorbol myristate acetate (PMA). AM from 11 sarcoid patients produced a mean (±SE) of 21.7±23 and 5.9±3.4 umol H202/10' macrophages in the presence and absence of PMA, respectively. By contrast, AM from normals (n = 6) produced 9.8±1.7 and 1.6±0.7 nmol H202/106 macrophages with and without PNMA, respectively. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…The increased H202 production was demonstrated for both stimulated and unstimulated cells. These results are similar to the data reported in adult inflammatory lung diseases such as sarcoidosis (26) and in children with interstitial lung diseases (2 1). The mechanisms by which these species may play a role in lung injury have been intensively investigated and many possibilities have been proposed.…”
Section: Discussionsupporting
confidence: 91%
“…The increased H202 production was demonstrated for both stimulated and unstimulated cells. These results are similar to the data reported in adult inflammatory lung diseases such as sarcoidosis (26) and in children with interstitial lung diseases (2 1). The mechanisms by which these species may play a role in lung injury have been intensively investigated and many possibilities have been proposed.…”
Section: Discussionsupporting
confidence: 91%
“…Several investigators have demonstrated that alveolar macrophages isolated from the BAL of sarcoidosis patients possess an enhanced capacity to metabolize oxygen and to produce hydrogen peroxide and superoxide anions, especially under the influence of activating substances [6,[13][14][15][16]. In accordance to these in vitro observed phenomena, the EBC of sarcoidosis patients has elevated levels of 8-isoprostane [8,9], whereas in the present study a systemic redox imbalance was also observed.…”
Section: Discussionsupporting
confidence: 86%
“…The generation of ROS has been previously observed in the chronic inflammatory environment of granulomatous lung diseases, such as sarcoidosis (12,13). Increased levels of glutathione and glutathione peroxidase have been measured in the epithelial lining fluid of patients with CBD, suggesting a role for the glutathione antioxidant system in granulomatous lung disease (14).…”
Section: Discussionmentioning
confidence: 86%